Reconstructing the value puzzle in health technology assessment: a pragmatic review to determine which modelling methods can account for additional value elements - Muir, Jeffrey M.; Radhakrishnan, Amruta; Freitag, Andreas; Ozer Stillman, Ipek; Sarri, Grammati (Frontiers in Pharmacology, 2023)
Health technology assessment (HTA) has traditionally relied on cost-effectiveness analysis (CEA) as a cornerstone of evaluation of new therapies, assessing the clinical validity and utility, the efficacy, and the cost-effectiveness of new interventions. The current format of CEA, however, does not allow for inclusion of more holistic aspects of health and, therefore, value elements for new technologies such as the impact on patients and society beyond its pure clinical and economic value. This study aimed to review the recent modelling attempts to expand the traditional CEA approach by incorporating additional elements of value in HTA. A pragmatic literature review was conducted for articles published between 2012 and 2022 reporting CEAs including value aspects beyond the clinical and cost-effectiveness estimates; searches identified 13 articles that were eligible for inclusion. These expanded modelling approaches mainly focused on integrating the impact of societal values and health equity in CEAs, both of which were championed as important aspects of HTA that should be incorporated into future technology assessments. The reviewed CEA methods included modification of the current CEA methodology (distributional CEA, augmented CEA, extended CEA) or the use of multi-criteria decision analysis. Of these approaches, augmented CEA appears to have the most potential by expanding traditional aspects of value, as it uses techniques already familiar to HTA agencies but also allows space for incorporation of qualitative aspects of a product's value. This review showcases that methods to unravel additional value elements for technology assessment exist, therefore, patient access to promising technologies can be improved by moving the discussion from "if" to "how" additional value elements can inform decision-making.